A Novel Modified-Curcumin Promotes Resolvin-Like Activity and Reduces Bone Loss in Diabetes-Induced Experimental Periodontitis - Deng J; Golub LM; Lee HM; Raja V; Johnson F; Kucine A; Lee W; Xu TM; Gu Y (Dove Medical Press, 2021)
Jie Deng,1 Lorne M Golub,2 Hsi-Ming Lee,2 Veena Raja,2 Francis Johnson,3 Allan Kucine,4 Wonsae Lee,5 Tian-Min Xu,1 Ying Gu6 1Department of Orthodontics, Peking University School and Hospital of Stomatology & National Clinical Research Center for Oral Diseases & National Engineering Laboratory for Digital and Material Technology of Stomatology & Beijing Key Laboratory of Digital Stomatology, Beijing, 100081, People's Republic of China; 2Department of Oral Biology and Pathology, School of Dental Medicine, Stony Brook University, Stony Brook, NY, 11794, USA; 3Department of Chemistry and Pharmacological Sciences, School of Medicine, Stony Brook University, Stony Brook, NY, 11794, USA; 4Department of Oral & Maxillofacial Surgery, School of Dental Medicine, Stony Brook University, Stony Brook, NY, 11794, USA; 5Department of Biomedical Engineering, Stony Brook University, Stony Brook, NY, 11794, USA; 6Department of General Dentistry, School of Dental Medicine, Stony Brook University, Stony Brook, NY, 11794, USACorrespondence: Jie DengDepartment of Orthodontics, Peking University School and Hospital of Stomatology & National Clinical Research Center for Oral Diseases & National Engineering Laboratory for Digital and Material Technology of Stomatology & Beijing Key Laboratory of Digital Stomatology, 22 Zhongguancun South Avenue, Haidian District, Beijing, 100081, People's Republic of ChinaTel +1 631 632-3172Fax +1 631 632-9705Email jie.deng917@gmail.comTian-Min Xu Email tmxuortho@163.comPurpose: Clinically, it is challenging to manage diabetic patients with periodontitis. Biochemically, both involve a wide range of inflammatory/collagenolytic conditions which exacerbate each other in a "bi-directional manner." However, standard treatments for this type of periodontitis rely on reducing the bacterial burden and less on controlling hyper-inflammation/excessive-collagenolysis. Thus, there is a crucial need for new therapeutic strategies to modulate this excessive host response and to promote enhanced resolution of inflammation. The aim of the current study is to evaluate the impact of a novel chemically-modified curcumin 2.24 (CMC2.24) on host inflammatory response in diabetic rats.Methods: Type I diabetes was induced by streptozotocin injection; periodontal breakdown then results as a complication of uncontrolled hyperglycemia. Non-diabetic rats served as controls. CMC2.24, or the vehicle-alone, was administered by oral gavage daily for 3 weeks to the diabetics. Micro-CT was used to analyze morphometric changes and quantify bone loss. MMPs were analyzed by gelatin zymography. Cell function was examined by cell migration assay, and cytokines and resolvins were measured by ELISA.Results: In this severe inflammatory disease model, administration of the pleiotropic CMC2.24 was found to normalize the excessive accumulation and impaired chemotactic activity of macrophages in peritoneal exudates, significantly decrease MMP-9 and pro-inflammatory cytokines to near normal levels, and markedly increase resolvin D1 (RvD1) levels in the thioglycolate-elicited peritoneal exudates (tPE). Similar effects on MMPs and RvD1 were observed in the non-elicited resident peritoneal washes (rPW). Regarding clinical relevance, CMC2.24 significantly inhibited the loss of alveolar bone height, volume and mineral density (ie, diabetes-induced periodontitis and osteoporosis).Conclusion: In conclusion, treating hyperglycemic diabetic rats with CMC2.24 (a tri-ketonic phenylaminocarbonyl curcumin) promotes the resolution of local and systemic inflammation, reduces bone loss, in addition to suppressing collagenolytic MMPs and pro-inflammatory cytokines, suggesting a novel therapeutic strategy for treating periodontitis complicated by other chronic diseases.Keywords: hyperglycemia, periodontitis, matrix metalloproteinases, inflammation, resolvins, host-modulatory therapy